Trade with developing countries and employment in the European Community - Dieter Schumacher (Intereconomics, 1981)
The opposition to a liberal stance on imports of manufactures from developing countries is growing as certain specific groups of products made in these countries prove increasingly competitive and the industrialized countries suffer from persistent high unemployment. Model computations for the six most important EC countries reveal however that the imports from developing countries have only a small impact on employment in these economies seen as a whole.
Keywords: 330; European Community